Prevalence of Hepatitis B and Hepatitis D Virus Infections in the United States, 2011–2016 - Patel, Eshan U.; Thio, Chloe L.; Boon, Denali; Thomas, David L.; Tobian, Aaron A. R. (Clinical infectious diseases, 2019)
Among adults in the 2011-2016 National Health and Nutrition Examination Survey (NHANES), the estimated prevalence of hepatitis B surface antigen (HBsAg) was 0.36% overall and 3.4% in non-Hispanic Asians. Among adult HBsAg carriers, 42% had antibodies to hepatitis delta virus (anti-HDV). Routine anti-HDV testing should be considered for HBsAg carriers.